Development of mortar for laying and coating with pineapple fibers - Azevedo, Afonso R.; Marvila, Markssuel T.; Zanelato, Euzébio B.; Alexandre, Jonas; Xavier, Gustavo C.; Cecchin, Daiane (Revista brasileira de engenharia agrícola e ambiental, 2020)
ABSTRACT Brazil is one of the largest producers of pineapple in the world, which, in addition to bringing substantial benefits, contributes to increasing waste generation in the stages of processing, aiming at its consumption. The Brazilian environmental legislation has been increasingly more restrictive with respect to the disposal of solid waste, whether domestic, industrial or agro-industrial, which has stimulated studies related to the use of these materials in several matrices. This study aimed to evaluate the potentiality of using the natural fiber of pineapple (Ananas comosus), extracted from its leaves, as reinforcing material in cementitious composites. For this purpose, natural fiber extracted from the pineapple crown was incorporated in different percentages in relation to the cement mass: 0, 2.5, 5, 7.5 and 10%, and the fibers obtained were submerged in aqueous NaOH solution with 5% concentration in volume, for 1 h at room temperature. The following variables were evaluated: consistency, water retention, incorporated air, mass density in hardened state, mechanical strength, water absorption by immersion and capillarity, besides verifying the influence of the mode of fiber incorporation. It was observed that the treatment with NaOH solution and the percentage of natural pineapple fiber incorporated in up to 5% in relation to the cement mass form mortars with technological feasibility. RESUMO O Brasil é um dos maiores produtores de abacaxi do mundo, o que além de trazer enormes benefícios contribui para o aumento da geração de resíduos nas etapas de beneficiamento, visando seu consumo. A legislação ambiental brasileira vem se tornando a cada ano mais restritiva quanto ao descarte dos resíduos sólidos, sejam domésticos, industriais ou agroindustriais, o que vem suscitando estudos relativos ao uso destes materiais em diversas matrizes. Esse trabalho visa avaliar a potencialidade da utilização da fibra natural do abacaxi, extraída da folha do abacaxizeiro (Ananás comosus) como material de reforço em compósitos cimentícios. Para este propósito, a fibra natural extraída da coroa do abacaxi foi incorporada em diferentes proporções em relação à massa de cimento: 0, 2,5, 5, 7,5 e 10%, e as fibras obtidas foram submersas em solução aquosa de NaOH com concentração de 5% em volume, durante 1 h à temperatura ambiente. Foram avaliadas as seguintes variáveis: consistência, retenção de água, ar incorporado, densidade de massa no estado endurecido, resistência mecânica, absorção de água por imersão e por capilaridade, além de verificar a influência do modo de incorporação das fibras. Foi observado que o tratamento com solução de NaOH e a porcentagem de fibra natural de abacaxi incorporada em até 5% em relação à massa de cimento formam argamassas com viabilidade tecnológica.